Study on the properties of CuSbS₂ and CuSbSeₓS₂₋ₓ thin films for photovoltaic and photodetector applications - Vinayakumar, Vineetha (2019)
The photovoltaic (PV) technology is of great interest in the present scenario owing to renewable energy production from natural resources such as solar light. At present, the PV technology markedly deals with the solar cells based on single crystalline Silicon. However, the production cost involved in the single crystalline Si-based solar cells accelerated the research towards much cheaper materials for a cost-effective technology. In this aspect, thin film solar cells are of great importance especially solar cells based on chalcogenide semiconductors without compromising much in the device performance due to their versatile properties. CuInGaSe2 and CdTe have come up with conversion efficiencies up to 21.7% and 21.5% which is comparable with the highest reported efficiency of 25.6% for a single-crystalline Si-based cell. Nevertheless, the price and inadequacy of In and Ga, as well as the toxicity of Cd, serves as barriers towards their practical applications. The research was then focused on other semiconducting materials having earth-abundant, low cost and non-toxic constituents. Different material systems were studied as a result including the Cubased compounds such as copper zinc tin sulfo selenide (CZTSSe) and copper zinc tin sulfide (CZTS). Due to issues such as complex structural polymorphism and cation stoichiometry of CZTSSe materials also face problems while incorporated as absorber layers in solar cells. Copper antimony sulfide (CuSbS2) is a novel chalcogenide semiconductor featuring suitable chemical and physical properties for being an absorber layer in solar cells as Antimony preserves the same chemistry as that of Indium and Gallium due to the similarities in their oxidation states as well as ionic radii. Additionally, CuSbS2 exhibits an optical band gap of 1.5 eV for direct transition, a high absorption coefficient of 104 cm−1 and Spectroscopic Limited Maximum Efficiency (SLME) of 22.9% which are some characteristic features required for an ideal photovoltaic absorber layer. This material has gained intense attention in the scientific community since it was first introduced by P.K. Nair et al. via heating of Sb2S3 and Cu2S layers. A lot of attempts have been made thereafter towards developing this material through different physical and chemical methods and subsequently integrating the same in PV devices. In the majority of the attempts, the conversion efficiency of the fabricated cells, however, remained very low compared to the present commercial PV technologies. The highest reported efficiency of a CuSbS2 based solar cell up to date is 3.22% where CuSbS2 was spin-coated using its precursor ink. In this thesis, we make a strong effort towards understanding different properties and device performance associated with this material. We used chemical bath deposition to prepare Sb2S3 thin films onto which the Cu layer was evaporated followed by heating to form the ternary CuSbS2 phase. The effects of different Cu thicknesses, heat treatments (rapid thermal processing, conventional vacuum oven annealing or both at different temperatures durations), were studied in detail on the semoconducting properties of CuSbS2 for PV applications. The structure, morphology, chemical composition and optoelectronic properties of the thin film formed at different conditions were analyzed using various characterization techniques such as XRD, Raman, SEM-EDX, XPS, UV-Vis spectroscopy, I-V and photocurrent response measurements. Device applications of the films which showed comparatively better properties were tested by incorporating them in solar cells as absorber layers. The best solar cell based on CuSbS2 showed an efficiency of 0.6% for the substrate p-n configuration, glass/ITO/n-CdS/p-CuSbS2/Ag. To further improve the efficiency, we alloyed CuSbS2 with selenium solid solution to fabricate quaternary CuSbSexS2−X. Our assumptions for alloying it with Se was ground on the fact that incorporation of Se can shift the bandgap of CuSbS2 from 1.5 to 1.2 eV depending on the Se content for much efficient solar light absorption. The champion cell featuring the quaternary CuSbSexS2−X as the absorber displayed a conversion efficiency of 0.91%, higher than the CuSbS2 based cells. In addition to the PV device application, we also explored the capability of the CuSbS2 in optoelectronic applications where it was tested as a photodetector for a wide range of wavelengths. For the first time ever, we found that CuSbS2 has great potential as a photodetector as well owing to its high sensitivity towards detection of different wavelength light. The synthesis procedure, characterizations, and device applications are explained in detail in different chapters of the thesis which can be really useful in understanding the distinct properties of both CuSbS2 and CuSbSexS2−X and towards further optimization to improve the conversion efficiencies where these compounds are used as absorbers.